OXYGEN ISOTOPE EQUILIBRIUM BETWEEN ULTRAHIGH-PRESSURE METAMORPHIC MINERALS AND ITS CONSTRAINTS ON SM-ND AND RB-SR CHRONOMETERS - Zheng Y.-F.; Zhao Z.-F.; Li S.-G.; Gong B. (My University, 2003)
In the Sm-Nd and Rb-Sr isotopic geochronology of metamorphic rocks, an important question is whether radiometric systems of mineral isochrons have achieved isotopic equilibrium during a given metamorphic event and preserved the equilibrium afterwards. An analogue to mineral chronometry is O isotope geothermometry. Because the rates of Sm-Nd, Sr and O diffusion in metamorphic minerals are comparable in many cases, the state of O isotope equilibrium between metamorphic minerals can provide a test for the validity of mineral Sm-Nd and Rb-Sr chronometers. In order to illustrate this applicability, O isotope geothermometry was carried out for Sm-Nd and Rb-Sr isochron minerals from ultrahigh-pressure (UHP) eclogites and gneisses at Shuanghe in the Dabie terrane of east-central China. Although the Sm-Nd isochrons give consistent Triassic ages of 213 to 238 Ma for UHP metamorphism, the Rb-Sr isochrons give Jurassic ages of 171 to 174 Ma for the same samples. O isotope geothermometry of the gneiss, eclogite and amphibolite minerals yields two sets of temperatures of 600 to 720 degrees C and 420 to 550 degrees C, respectively, corresponding to cessation of isotopic exchange by diffusion at about 225 +/- 5 Ma during high pressure eclogite-facies recrystallization and at about 175 +/- 5 Ma during amphibolite-facies retrogression. The preservation of Triassic Sm-Nd isochron ages, but the occurrence of Jurassic Rb-Sr isochron ages and the regular O isotope temperatures for the same samples, suggest that rates of Sr and O diffusion in such hydroxyl-bearing minerals as biotite and hornblende are faster than rates of Nd diffusion in garnet and Sr diffusion in phengite on the scale of a hand-specimen during the amphibolite-facies retrogression. While the mineral with slow diffusivity has exerted the primary control on the homogenization rate of initial isotope ratios among isochron minerals during retrograde metamorphism, the mineral with high parent/daughter ratio has exerted the principal control on the initiation of the mineral isochron clock in response to retrogression. Valid mineral isochrons can be expected to date the timing of metamorphic resetting only if the mineral with high parent/daughter ratio has a fast rate of radiogenic isotope diffusion during the metamorphic resetting.